2003
DOI: 10.1002/pri.283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manual hyperinflation on haemodynamics in an animal model

Abstract: Significant haemodynamic changes occurred in this animal model. The increased intrathoracic pressure, applied for an increased period during inspiration, decreased cardiac output with compensatory vasoconstriction evident by the increased systemic vascular resistance and mean arterial pressure. The results suggest that there may be a decrease in cardiac output after increased positive pressure in subjects with normal cardiac and respiratory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…(4,9,19) A previous randomized clinical trial has shown that the use of a positive expiratory pressure (PEP) mask can significantly increase mean arterial pressure, mean pulmonary artery pressure, central venous pressure and pulmonary artery occlusion pressure. However, these differences were considered not to have a relevant harmful clinical impact on hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4,9,19) A previous randomized clinical trial has shown that the use of a positive expiratory pressure (PEP) mask can significantly increase mean arterial pressure, mean pulmonary artery pressure, central venous pressure and pulmonary artery occlusion pressure. However, these differences were considered not to have a relevant harmful clinical impact on hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…(9) These data were chosen because, to the best of our knowledge, the study from which it came was the most similar to ours at the time of the study design. Heart rate, MAP, and pulmonary artery pressure were used as the main endpoints.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also demonstrated clinically significant decreases in CO in an animal model with normal cardiac function during MHI. 41 An FiO 2 of 1.0 was used during MHI because it was believed that if alveoli were recruited by the hyperinflation procedure, desaturation caused by pulmonary hypoxemic vasoconstriction may have occurred. 42 This, however, could have had an effect on hemodynamics because an FiO 2 of 1.0 can decrease CO and peripheral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…3 A study group in Australia used a healthy adult sheep model to evaluate variability in the performance of manual physical therapy by physiotherapists. 4,5 Adult rabbits were used as an experimental model in Japan, in studies of the effectiveness of rib cage compression in removing secretions and improving the resolution of obstructive atelectasis, 6,7 and the effectiveness of physical therapy techniques in removing secretions from the trachea, using a meconium aspiration syndrome model. 8 Brazilian researchers proposed a model that mimics respiratory physiotherapy in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%